Description of the content of some heavy metals in the foodstuffs that are the food intake of the Transcarpathian region - Yerem, T.V. (Environment & Health, 2015)
Objective. We studied the quantitative content of the heavy metals in the vegetable blend, grown on the territory of the Transcarpathian region that was a food intake of the local population. Materials and methods. We used such research methods of the study of microelement composition of vegetable blend: instrumental-and-laboratory, sanitary-and-chemical. All the digital data, obtained during the experiments, were processed by the methods of variation statistics. Results. In the course of our study we proved the presence of a low concentration of heavy metals in the food intakes of the inhabitants of the Transcarpathian region. Conclusions: The obtained data suggest that studied samples of the vegetable blend, comprising a food intake of the residents of the Transcarpathian region, should be considered ecologically pure by the content of lead and mercury. In case of their application they cannot be a reason of dangerous changes in the health state of the population. Monitoring of the content of heavy metals in the vegetables of the Transcarpathian region should be continued not only for current control of the quality of the foodstuffs, but also for the accumulation of the results of laboratory studies of heavy metals in the products of all areas of the region taking into account hydrogeological, agrochemical, climate-and-weather, and other conditions for the cultivation of the agricultural crops; storage, and processing, transportation of the foodstuffs.